Association of Serum testosterone Level with Depression in Parkinsons Disease (Bangladesh Journal of Neuroscience, 2014)
Background: Depression is a non-motor symptom in Parkinsons disease (PD) as well as elderly population due to testosterone deficiency (TD). Because of similarity between depression in PD and for testosterone deficiency, clinician may fail to recognize and treat TD in patients with PD. Objectives: Our aim was to find out the association between serum total testosterone level and depression in men with Parkinson disease. Methods:This was a case control study carried out in the OPD of department of Neurology, Department of Psychiatry and Department of Biochemistry, Bangabandhu Sheikh Mujib Medical University (BSMMU) on total of 64 subjects where 34 were cases and 30 were controls age ranging from 40 to 85 years of age. Results: This analysis showed serum testosterone levels were significantly low in PD patients with depression compared to controls ( 4.90±1.86 ng/ml in cases and 6.66±1.18 ng/ml in control group with Odds ratio is 2.071; 95% CI 1.587-2.704). Significantly (P